2009
DOI: 10.1099/mic.0.027920-0
|View full text |Cite
|
Sign up to set email alerts
|

The OxyR homologue in Tannerella forsythia regulates expression of oxidative stress responses and biofilm formation

Abstract: Tannerella forsythia is an anaerobic periodontal pathogen that encounters constant oxidative stress in the human oral cavity due to exposure to air and reactive oxidative species from coexisting dental plaque bacteria as well as leukocytes. In this study, we sought to characterize a T. forsythia ORF with close similarity to bacterial oxidative stress response sensor protein OxyR. To analyse the role of this OxyR homologue, a gene deletion mutant was constructed and characterized. Aerotolerance, survival after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 43 publications
(92 reference statements)
3
47
1
3
Order By: Relevance
“…This transcription factor is involved in the expression of pili in S. marcescens (46) and Porphyromonas gingivalis (50), the regulation of Ag43 biosynthesis in E. coli (22), and in biofilm formation in many bacteria (9,24,31,44,46). In the present study, we found a decrease in the expression of types 1 and 3 pilus genes for the K. pneumoniae oxyR mutant compared to the parental strain, as well as a decreased ability to form biofilm on static polystyrene microtiter plate.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…This transcription factor is involved in the expression of pili in S. marcescens (46) and Porphyromonas gingivalis (50), the regulation of Ag43 biosynthesis in E. coli (22), and in biofilm formation in many bacteria (9,24,31,44,46). In the present study, we found a decrease in the expression of types 1 and 3 pilus genes for the K. pneumoniae oxyR mutant compared to the parental strain, as well as a decreased ability to form biofilm on static polystyrene microtiter plate.…”
Section: Discussionsupporting
confidence: 45%
“…In E. coli, OxyR enhances the ability of the bacteria to colonize the urinary tract (27). However, OxyR was first reported to play a role in the oxidative stress response (24,31,44,46,47,52). In E. coli, the OxyR transcription factor activates the expression of several antioxidant defensive genes in response to elevated levels of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ) (20,26).…”
mentioning
confidence: 99%
“…Contrarily, the oxyR mutants of E. coli (45) and Burkholderia pseudomallei (46) are biofilm hyper-formers. OxyR has been known to regulate the formation of cell appendages and biofilm in pathogenic bacteria, which is important for their attachment to biotic/abiotic surfaces and for virulence (18,43,45); however, the mechanisms that relate oxidative stress defense and biofilm formation are poorly understood at present (19). In V. parahaemolyticus, the rapid biosynthesis of exopolysaccharides, flagella, and other biofilm-or motility-associated factors may accompany the generation of ROS, and thus the lowered expression of catalase/AhpC in the oxyR mutant may impair its biofilm formation ( Table 6).…”
Section: Figmentioning
confidence: 99%
“…The expressions of catalase and ahpC genes are usually regulated by OxyR (12), which is a redox-sensitive transcriptional regulator of the LysR family in Escherichia coli, Salmonella spp., and other bacteria (13-17). OxyR also participates in pathogenesis by promoting biofilm formation, fimbrial expression, and mucosal colonization in pathogenic bacteria (18); nevertheless, the mechanism of oxidative stress defense in these phenomena is not clear (19).The function of oxyR has been examined in a few Vibrio species but not in V. parahaemolyticus. The effect of oxyR on the survival of bacteria and on their viable but nonculturable state has been investigated in Vibrio vulnificus (20)(21)(22) and in Vibrio harveyi (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation